Cruz de Deus, cruz do povo. concepções e práticas de devoção à cruz na “Caminhada Santa Cruz”, norte de Minas Gerais - Dias, Juliana Aparecida Silva Farias (2016)
This study aims to evaluate the devotional rituals to the cross in Santa Cruz Walking inrural communities of Machados, Lages and Santa Rita de Santa Cruz, north of Minas Gerais. The walking is a practice whose rituals date back to the seventeenth century in the region of mines and was taken up by residents without the presence of members of the ecclesiastical hierarchy. Here‘s this study‘s problem: how such a practice is kept alive in a time when society is more urban than rural; that is to say, how a distinctive religious phenomenon of a religiosity of colonial times reaches the XXI century. Such research problem is outlined in these questions: what is the origin of devotion to the holy walking? Why devotees interrupt their routine to dedicate their time to the walking? What does the cross mean to the devotees? In search of answers, this study tries to write a history of this holy walking — written records of which are too scarce— and to outline the imaginary cross permeating the practice of devoting. An initial hypothesis is that the representation of the cross among current participants of the walking was linked to their everyday culture and tradition, and that such representation was influenced by continuous changes in regional religious field. A study on specific bibliography guided the observation of the community walking — where it takes place and so that lean more of its organization and rituals — in three cruises during 2013 and 2014. Observations were recorded with photographs and field notes. Questionnaires and interviews were used in the light oral history methodology to build the history of the holy walking with the support from historical and anthropological approaches. The conclusion is that devotion have arisen in the context of a popular Catholicism as to an untying from ecclesiastical hierarchy — such is the way it was practiced in colonial Brazil — and that the practice on that same place was born a century ago. After an interruption of nearly 13 years, the holy walking practice took place again but this time accordingly with needs and devotional goals of current practitioners, that put aside their daily activities to devote themselves to the event. Exorcism prayers and use of the sign of the cross over and over again in ―defense against the enemy‖ revealed the mystical dimension of devotion to the cross in the imagination of this devout group, where its singularity. That said, this study‘s relevance to the religious studies includes revisiting a classic theme and an empirical investigation